Dynamics of Indonesian Foreign Policy at the United Nations General Assembly - Abdurofiq, Atep; Putra, Gilang Rizki Aji; Yunus, Nur Rohim (UIN Jakarta, 2024)
Indonesia's foreign policy at the United Nations (UN) General Assembly reflects the complexity of the country's problems and opportunities in global diplomacy. Indonesia, as the world's largest democratic country and with the largest Muslim population, plays a vital role in advocating for peace, justice and sustainable development on the global stage. However, amidst changing geopolitical dynamics, Indonesia faces many obstacles that hamper its capacity to shape international policy. This article will explore sovereignty, territorial integrity, human rights, peace and security, and sustainable development to understand how Indonesia can take advantage of existing opportunities and overcome the obstacles it faces to take a more prominent position in this global forum. This article will comprehensively study the dynamics of Indonesia's foreign policy at the UN.